Measurement of saliva flow rate in healthy young humans: influence of collection time and mouthrinse water temperature. (27th September 2016) - Gill, Samantha K.; Price, Mike; Costa, Ricardo J. S.
Abstract : The aim of the current study was to determine if unstimulated saliva flow (measured in μ l min −1 ) is affected by different durations of sample collection and by temperatures of mouthrinse water used before sample collection. In randomized order, participants provided 10 samples of unstimulated saliva at time points ranging from 1 to 6 min after rinsing with different temperatures of water (10, 20, and 30°C). Data were analysed by one‐wayanova with post‐hoc tests. Test–retest reliability was assessed using Bland–Altman plots and correlation coefficients. A larger volume of saliva was obtained over a longer collection time. No significant difference in saliva flow rate was observed between collection times [mean: 364 (95% CI: 332–397) μ l min −1 ]. Although rinsing with different temperatures of mouthrinse water resulted in no significant difference in saliva flow rates as a result of the mouthrinse water temperatures, 60% of the participants had a higher saliva flow rate after rinsing with mouthrinse water at a temperature of 10°C compared with mouthrinse water at 20 and 30°C, suggesting large individual variation (range: 24–420 μ l min −1 ). These findings provide justification for using saliva collection times of 1–6 min during sampling of unstimulated saliva. The large individual variations in saliva flow rate in response to different mouthrinse water temperatures suggest that standardization, control, and reporting of mouthrinse water temperature is warranted.